Rotational motions of the boat (Rowing Biomechanics Newsletter, 2012)
This article deals with the rotational motions of the boat at the three main axes in any vessel, called longitudinal X, lateral or transverse Y and vertical Z axes (Fig.1). The rotational movements around them are known as roll, pitch and yaw: · Roll is when the boat rotates about the longitudinal X (front/back) axis. · Pitch is when the boat rotates about the lateral or transverse Y (side-to-side) axis. · Yaw is when the boat rotates about the vertical Z (up-down) axis.